LEARNING POLICY ADVICE IN INTERNATIONAL AFFAIRS AND DIPLOMACY - Venneri, Giulio (ROUTLEDGE, 2025)
Learning Policy Advice in International Affairs and Diplomacy broadens understanding of, and helps develop the skills necessary for, effective written and oral communication in the realm of international affairs and diplomacy. Readers will become acquainted with the principles of policy development and find practical guidance on how to design and implement policy advice. Crucial insights are offered on how to successfully nurture those aptitudes and approaches that are expected in demanding professional contexts from the very start of a career. Effective drafting techniques for written communication are presented, explaining methods and practices that facilitate the delivery of meaningful policy advice through written output. Regarding oral communication, the book demonstrates how aspiring policy advisers can build a positive narrative about their background, profile and experience, in order to win over selection panels for jobs across the international community. The book explains how to tackle interview panels, and prove to recruiters the necessary competence, skills, vision, and motivation to perform efficiently and reliably in an international or EU policy role. By raising awareness of institutional communication practices and public outreach, the book will also give readers a sound understanding of perception management challenges in international politics and diplomacy. Building on twenty years' experience as a policy insider in the international community, the author provides qualitative interviews with many other practitioners, including high-ranking officials, from different organisations and foreign services, as well as with scholars who have alternated academic engagement with appointments to key policy roles in diplomacy. Containing example scenarios and practice exercises throughout, this pioneering book helps students, graduates and professionals aspiring to build a career in international affairs to acquire practical skills which are essential to recruiters in the diplomatic world, international institutions, NGOs, think tanks, as well as the private sector.